Reframing Vocabulary Learning in Rural EFL Education: Memrise-Assisted Project-Based Learning and Student Engagement in Indonesia - Rahmayani Kadir; La Sunra; Andi Asrifan (Foreign Language Instruction Probe, 2026)
This study examined the application of Memrise-assisted Project-Based Learning to enhance vocabulary proficiency and student engagement in a rural Indonesian EFL classroom. The study examined the impact of a gamified mobile-assisted learning platform on students' vocabulary acquisition, classroom engagement, and collaborative learning during project-based instructional activities. The study utilized a Classroom Action Research design with a mixed-methods approach, involving 24 tenth-grade students at a rural secondary school in West Sulawesi, Indonesia. Data were gathered via vocabulary pre-tests and post-tests, classroom observations, reflective journals, interviews, and documentation. Quantitative data were analyzed using mean score analysis and paired-sample t-tests, supplemented by qualitative thematic interpretation. The results indicated a significant enhancement in students' vocabulary performance across the research cycles, with average scores rising from 53.4 in the initial phase to 69.8 in Cycle I and 83.1 in Cycle II. Student involvement, teamwork, confidence, and the use of contextual vocabulary significantly improved following instructional modifications. The findings indicate that integrating gamified mobile-assisted vocabulary learning with Project-Based Learning can convert vocabulary instruction from a memorization-focused approach to a more significant, interactive, and contextually relevant learning experience, especially in under-resourced rural EFL settings.